El Excentrico, 1964-02-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
February 20, 1964 [20 de febrero de 1964]. Ano 14, No 9. Cover has a photograph of people promoting yhe United Food Drive campaign, with headline "United Food Drive Committee Officers - 17th Year."